Relationship between Livestock Pen Sanitation, Fly Density, Well Conditions, and Diarrhea Incidence in Aek Banir Village, Panyabungan District - Hamdani, Dinda Putri; Indirawati, Sri Malem (Universitas Muhammadiyah Surakarta, 2025)
Introduction: Inadequate livestock pen sanitation has been demonstrated to increase fly populations in the surrounding environment, thereby elevating the risk of diarrhea transmission among communities living in proximity to the pens. Additionally, wells constructed without adherence to proper construction standards have been associated with an elevated risk of water contamination, which, in turn, can lead to an increased incidence of diarrhea. The objective of this study is to ascertain the correlation between livestock pen sanitation, fly density, and well conditions with diarrhea incidence in the community of Aek Banir Village, Panyabungan Sub-District. Method: A quantitative approach with a cross-sectional design was utilized, involving 40 livestock owners as the sample, selected through total sampling. The collection of data was executed through the utilization of observation sheets, questionnaires, and fly grills. The analysis of the data was conducted using the chi-square test and Fisher's Exact Test. Results: The results indicated that 60.0% of livestock pens did not meet sanitation standards, 52.5% exhibited high fly density, 50.0% of wells were in poor condition, and 55.0% of livestock owners had experienced diarrhea. The chi-square test with Fisher's Exact Test indicated a significant relationship between livestock pen sanitation, fly density, and well conditions with the incidence of diarrhea. Conclusion: The present study posits that there is a relationship between livestock pen sanitation, fly density, and well conditions with diarrhea incidence in the community of Aek Banir Village, Panyabungan Subdistrict.